Pengaruh Penggunaan Perangkat Digital Terhadap Timbulnya Computer Vision Syndrome Pada Mahasiswa Fakultas Kedokteran - Ananda Fadilah; Eri Dian Maharsi (Junior Medical Journal, 2022)
Background: Computer Vision Syndrome (CVS) is an umbrella term for symptom patterns associated with prolonged exposure to digital screens, such as eye fatigue, headaches, blurred vision, and dry eyes. The number of internet users in Indonesia reached 88 million people until the end of 2014. Purpose: To determine the effect of the use of digital devices on the emergence of CVS on students of the medical faculty of YARSI University. Method: Analytical research with a cross sectional approach. The population and sample of this study are all students of the Faculty of Medicine, YARSI University class of 2020. Sampling technique using purposive sampling technique. This type of research data is primary data by questionnaire method. Data analysis is carried out univariately and bivariately. Research Results: Respondents who met the inclusion criteria were 140. The results showed that respondents who used digital devices received a frequency of use very often 38.6%, often 29.3%, while 27.9% and rarely 4.3%. Respondents' posture when using digital devices is sitting back 72.9%, sitting without a backrest of 23.6% and lying down 3.6%. Respondents who experienced 85% tired eyes, dry eyes 52.1%, blurred eyes 62.9%, headaches 63.6%, watery eyes 53.6% and CVS 85%. The results of the Chi Square test in all posture groups when using the device against the onset of CVS showed a p value value of more than 0.05, which means posture does not affect CVS. Meanwhile, in the duration group, the p value result is obtained in the comparison between the medium group and very often against the emergence of CVS, which is 0.017, which means that there is a meaningful relationship. Conclusion: Of the 140 respondents 85% complained of CVS. CVS is not affected by posture while duration for more than 8 hours in the use of the device affects the occurrence of CVS. Keywords: Digital Devices, Computer Vision Syndrome, Faculty of Medicine Students